If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (A + b) + 3 = 0 Remove parenthesis around (A + b) A + b + 3 = 0 Reorder the terms: 3 + A + b = 0 Solving 3 + A + b = 0 Solving for variable 'A'. Move all terms containing A to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + A + -3 + b = 0 + -3 Reorder the terms: 3 + -3 + A + b = 0 + -3 Combine like terms: 3 + -3 = 0 0 + A + b = 0 + -3 A + b = 0 + -3 Combine like terms: 0 + -3 = -3 A + b = -3 Add '-1b' to each side of the equation. A + b + -1b = -3 + -1b Combine like terms: b + -1b = 0 A + 0 = -3 + -1b A = -3 + -1b Simplifying A = -3 + -1b
| 25xsquared-16=0 | | 3a+45+2a-10=180 | | .75n-2=-.875n+32 | | 3X-16=2N+18 | | 11x+10x=12x | | 5sinx+4cosx=0 | | 8c-(c-1)=9 | | -5x^2+39x+8=0 | | -24=3v+4(v+8) | | 4y+y+1=7y | | 3x-8+x+26=180 | | 6x-5(x-7)=-10 | | -24=3v+4(4+8) | | -5(r+7)=-87 | | 50+3x=x+82 | | -2=7(x-6)-2x | | 3x-7=5x-45 | | 9+8(5x+3)=-3-5(8x+3) | | -8x+9=-8x+5 | | -3.5x^2+42t+13=0 | | -3(2x-3)=4(x-7) | | 4(6x+2)=8(3x+1) | | .03x+.12(20)=.06+20+x | | 0.03=0.01+2.9 | | x^2-14x=-46 | | 46+12x=17x | | 1.2+12.2= | | 6x^2-38=0 | | -12+a=4 | | abc+dbc= | | 6T-20=-21+5T | | P(x)=-x^2+10x-22 |